Resolving Sharia Economic Disputes In Indonesia: Principles, Legal Frameworks, And Implementation Challenges - Hafizd, Jefik Zulfikar; Mukhlas, Oyo Sunaryo; Hakim, Atang Abd. (FOCUS: Jurnal of Law, 2024)
The resolution of Sharia economic disputes requires compliance, stability, public trust, and protection of rights and business relationships. This qualitative research uses a normative juridical approach with library research to analyze the Sharia economic dispute resolution system in Indonesia. The study covers Sharia economic disputes, Sharia principles, the authority of Religious Courts, dispute resolution methods, and challenges in implementing Sharia principles. The findings show that Sharia economic disputes arise from transactions or activities based on Islamic principles. Key principles in dispute resolution include justice, Sharia compliance, consultation, agreement, confidentiality, consensus, and non-discrimination. Religious Courts have exclusive authority over Sharia economic cases based on Law No. 3/2006, the Constitutional Court Decision No. 93/PUU-X/2012, and Supreme Court Regulation No. 14/2016. Disputes can be resolved through litigation or non-litigation methods such as mediation or arbitration. Challenges include limited legal awareness, legal complexity, infrastructure issues, legal harmonization, and differing interpretations.